The Everest Years : A Climber's Life - Bonington, Chris (London Hodder & Stoughton, 1986)
The third volume of Chris Bonington's memoirs chronicles Bonington's four expeditions to the world's highest peak and his obsession with this most treacherous of mountains
Include Color Illustration, Bibliography and Index
Keywords: Mountaineers -- Asia--Mount Everest -- Mountaineering